The Effect of Promotion and Price of Electrifying Vehicle PLN on Consumer Decisions to use Electric Vehicles and its Impact on Consumer Satisfaction (Study at PT. PLN (Persero) UP3 North Banten) - Saripudin, Ruslan; Rizal, Alimuddin (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The title of this research is The Influence of PLN's Electrifying Vehicle Promotion and Price on Consumer Decisions to Use Electric Vehicles and Its Impact on Consumer Satisfaction; A Study at PT. PLN (Persero) UP3 North Banten. The purpose of this research is to analyze the promotion and perception of PLN's electrifying vehicle price influence on consumer decisions to use electric vehicles and impact on consumer satisfaction. The research method used is a quantitative method with a type of relationship that explains the relationship between independent, intervening and dependent variables. Data analysis with correlation analysis, determination analysis and regression analysis, where the data source is the respondents' answers to the questionnaire they received, with a sample size of 96. The results of the research show that the promotion and perception of PLN's electrifying vehicle price influence consumer decisions to use electric vehicles and impact on consumer satisfaction which is derived into seven research hypotheses. The main suggestion of the research is that the Management of PT. PLN (Persero) UP3 North Banten must be able to campaign for the transition of vehicles with fossil fuels to electric fuels, because it is relatively more environmentally friendly and cheaper.